Biomaterial-mediated presentation of wnt5a mimetic ligands enhances chondrogenesis and metabolism of stem cells by activating non-canonical Wnt signaling. (February 2022) - Deng, Yingrui; Zhang, Xiaoting; Li, Rui; Li, Zhuo; Yang, Boguang; Shi, Peng; Zhang, Honglu; Wang, Chunming; Wen, Chunyi; Li, Gang; Bian, Liming
Abstract: The presentation of development-relevant bioactive cues by biomaterial scaffolds is essential to the guided differentiation of seeded human mesenchymal stem cells (hMSCs) and subsequent tissue regeneration. Wnt5a is a critical non-canonical Wnt signaling ligand and plays a key role in the development of musculoskeletal tissues including cartilage. Herein we investigate the efficacy of biofunctionalizing the hyaluronic acid hydrogel with a synthetic Wnt5a mimetic ligand (Foxy5 peptide) to promote the chondrogenesis of hMSCs and the potential underlying molecular mechanism. Our findings show that the conjugation of Foxy5 peptide in the hydrogels activates non-canonical Wnt signaling of encapsulated hMSCs via the upregulation expression of PLCE1, CaMKII-β, and downstream NFATc1, leading to enhanced expression of chondrogenic markers such as SOX9 . The decoration of Foxy5 peptide also promotes the metabolic activities of encapsulated hMSCs as evidenced by upregulated gene expression of mitochondrial complex components and glucose metabolism biomarkers, leading to enhanced ATP biosynthesis. Furthermore, the conjugation of Foxy5 peptide activates the non-canonical Wnt, PI3K-PDK-AKT and IKK/NF-κB signaling pathways, thereby inhibiting the hypertrophy of the chondrogenically induced hMSCs in the hydrogels under both in vitro and in vivo conditions. This enhanced chondrogenesis and attenuated hypertrophy of hMSCs by the biomaterial-mediated bioactive cue presentation facilitates the potential clinical translation of hMSCs for cartilage regeneration. Our work provides valuable guidance to the rational design of bio-inductive scaffolds for various applications in regenerative medicine. Graphical abstract: Image 1